2018
DOI: 10.4236/ojo.2018.84019
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Fibromyxoid Sarcoma in the Left Gluteal Region Presenting as Sciatic Nerve Pain

Abstract: Low-grade fibromyxoid sarcoma is a slowly growing soft tissue neoplasm, mostly affecting young individuals. It usually arises in a deep soft tissue of the lower limbs and trunk, but few cases of low-grade fibromyxoid sarcoma that presents sciatic nerve pain have been reported. We report a 34-year-old woman with a low-grade fibromyxoid sarcoma originating in the left gluteal region that initially presented as sciatic nerve pain; she had experienced this type of pain for 5 years before visiting our hospital. Mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…To date, the relevant reports on sciatic nerve tumours misdiagnosed as LDH are case reports [ 4 10 , 14 , 20 , 21 ]. We systematically reviewed these reported cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the relevant reports on sciatic nerve tumours misdiagnosed as LDH are case reports [ 4 10 , 14 , 20 , 21 ]. We systematically reviewed these reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…The common clinical manifestations of these patients usually include sciatica, followed by atrophy, tenderness on deep intragluteal palpation, positive Tinel’s sign, positive Laseque’s sign, plantar flexion weakness, and a decreased ankle reflex [ 4 14 ]. It is worth considering that when patients present with unrelenting pain at rest, the possibility of tumours should be borne in mind, and proper imaging techniques should be used [ 10 , 11 , 14 , 15 ]. In 2019, Fernando Guedes et al [ 5 ] reported a patient with low-grade sarcoma who was misdiagnosed with LDH.…”
Section: Introductionmentioning
confidence: 99%